(untitled) (Jurnal Riset Manajemen Akuntansi Indonesia, 2025)
This research was conducted at Shilla Convection having its address at Mandungan, Wiro, Bayat, Klaten. The purpose of this study was to determine and analyze employee job satisfaction at Shilla Convection. The population in this study were employees at Shilla Convection as 15 respondents and 5 sources of whom were taken samples in this study who were considered competent. The methods used in this research are quantitative methods (descriptive statistics) and qualitative methods (Miles and Huberman). From the results of the research that the author did, the answer was obtained, satisfaction with superiors (supervision) was still not good because the average answer of respondents was 3.00 which showed a neutral attitude which could mean that respondents agreed or disagreed. Compared with satisfaction with the job itself, satisfaction with co-workers, satisfaction with benefits, satisfaction with promotion opportunities, satisfaction with salary, satisfaction with supportive working conditions which shows an average answer of 4.00 which indicates an attitude of agreement and can be interpreted as being satisfied. From the results of interviews it can be concluded that 2 people are quite satisfied working at Shilla Convection, while 3 other people are not satisfied with the attitude of their superiors and also with the bonuses/allowances given.